Performance analysis of signal processing algorithms for wall clutter mitigation and contrast target detection - Singh A.P. (My University, 2025)
The presence of clutter in through-the-wall images significantly degrades image quality and hampers the performance of algorithms used for data processing in tasks such as target detection, identification, or reconstruction. Real building walls exhibit inherent inhomogeneities, featuring varying frequency and spatial properties that defy the assumption of a smooth surface. Consequently, they produce nonuniform wall surface reflections at each scanning position. Furthermore, these walls often incorporate supply pipes that introduce substantial clutter, which, although stronger than the target responses, remains weaker than the wall surface clutter. Additionally, this clutter often exhibits signatures similar to those of the target. In real-world scenarios, target reflections can manifest as wide, flat hyperbolas or nearly straight lines, and they may be positioned near the wall. Consequently, distinguishing targets from clutter becomes a complex challenge. Various clutter reduction methods have been proposed in recent years, showing varying degrees of success. However, the effectiveness of these methods in the literature is inconsistent and sometimes contradictory. To address this issue, a comprehensive investigation of well-established clutter reduction methods was conducted to evaluate their performance under identical conditions. These methods were rigorously assessed using practical radar-measured data acquired in the presence of actual building wall materials and contrasting targets. Evaluation criteria include the target-to-clutter ratio and peak signal-to-noise ratio. The results of the experiment revealed that independent component analysis outperformed other clutter reduction methods, demonstrating superior performance in mitigating clutter and enhancing target detection. © 2024 Wiley Periodicals LLC.